Mixed Metal Oxides and Catalysis - Kumari, Sima; Kumar, B.; Kumar, R.; Bhagat, S. (Asian Journal of Chemistry, 2016)
Mixed metal oxides particularly the perovskites have been found to be excellent catalysts of great versatility and diversity. Analysis of the kinetic results obtained for the thermal degradation of urea using GdCoO3 and GdNiO3, as catalysts in terms of the basic concept of thermodynamics has led to the observation of “a family of catalysts” in close analogy to a family of reactions well defined and explained in literature. However, much more results are needed to corroborate this observation.